2012
DOI: 10.3736/jcim20121223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naringenin on allodynia and hyperalgesia in rats with chronic constriction injury-induced neuropathic pain

Abstract: The results of the present investigation suggest that naringenin exhibits analgesic effect in sciatic nerve injury model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…[73] Naringenin (8) (25 and 50 mg/ kg) showed ameliorating action against chronic constriction injury-induced neuropathic pain in sciatic nerve injury model through mechanisms of inhibition of NO pathway and ameliorating oxidative stress. [48] Biflavonoids is one of structurally unique classes of naturally occurring bioflavonoids which also have inhibitory effects on pain. Volkensiflavone (53), fukugetin (54), fukugeside (55).…”
Section: Apigenin Apigeninmentioning
confidence: 99%
“…[73] Naringenin (8) (25 and 50 mg/ kg) showed ameliorating action against chronic constriction injury-induced neuropathic pain in sciatic nerve injury model through mechanisms of inhibition of NO pathway and ameliorating oxidative stress. [48] Biflavonoids is one of structurally unique classes of naturally occurring bioflavonoids which also have inhibitory effects on pain. Volkensiflavone (53), fukugetin (54), fukugeside (55).…”
Section: Apigenin Apigeninmentioning
confidence: 99%
“…Estrogen deficiency causes an increase in nociceptive sensitivity (14). A high bone turnover, such as with postmenopausal osteoporosis, might augment skeletal pain via activation have demonstrated that pregabalin (10 ~ 40 mg/kg) improves the mechanical allodynia in the von Frey filament test caused by CCI (8,35). The difference between ours and previous reports could be because the weekly dose of pregabalin (10 mg/kg) in the present study may not have been enough to improve mechanical allodynia in our ovariectomized and CCI model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, JB have been reported to contain various bioactive compounds such as naringenin, apigenin and luteolin which have been reported to exhibit antidepressant, anti-neuroinflammation, anti-oxidant and cytoprotective effects [14] [15] [17] [38]. Apigenin and naringenin were also reported to exhibit analgesic activity in various acute and chronic animal models of pain [39] [40]. Also, naringenin and luteolin were shown to increased memory performance and to reverse scopolamine-induced amnesia in rodents through inhibition of AChE activity and oxidative stress-related processes [38] [41].…”
Section: Discussionmentioning
confidence: 99%